Cerebrovascular Neurosurgery in Evolution: The Endovascular Paradigm. (1st February 2014) - Sorkin, Grant C.; Dumont, Travis M.; Eller, Jorge L.; Mokin, Maxim; Snyder, Kenneth V.; Levy, Elad I.; Siddiqui, Adnan H.; Hopkins, L. Nelson
Abstract: Endovascular technique represents an important, minimally invasive approach to treating cerebrovascular disease. In this article, we discuss the origins of endovascular neurosurgery as a discipline in the context of important technical milestones, evidence-based medicine, and future cerebrovascular neurosurgical training. Cerebrovascular neurosurgery has seen a steady, convergent evolution toward the surgeon capable of seamless incorporation of open and endovascular approaches to any complex vascular disease affecting the central nervous system. Neurosurgery must assume the leadership role in the multidisciplinary neurovascular team.